2012
DOI: 10.3846/bjrbe.2012.26
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory evaluation of organic and chemical warm mix asphalt technologies for SMA asphalt

Abstract: Warm mix asphalt (WMA) technologies allow significant lowering of the production and paving temperature of the conventional hot mix asphalt (HMA), which promise various benefits, e.g. lowering the greenhouse gas emissions, reduction of energy consumption, improved working conditions, better workability and compaction, etc. However, in order to reach widespread implementation of WMA, it is necessary to prove that it has the same or better mechanical characteristics and long-term performance as HMA. This article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 3 publications
0
10
0
2
Order By: Relevance
“…Bonaquist (2011b) reports low temperature grade reduction between 0.5 to 3°C, depending on the technology and production temperature, which promises increased resistance to low temperature cracking of asphalt pavement. However, while Bonaquist's study did not show such an effect, some other studies have reported that the addition of wax might increase the low temperature grade by 2-3°C (Wanger et al 2008;Chowdhury and Button 2008) and Fraas temperature by 1-5°C (Zaumanis et al 2012b).…”
Section: Crackingmentioning
confidence: 52%
“…Bonaquist (2011b) reports low temperature grade reduction between 0.5 to 3°C, depending on the technology and production temperature, which promises increased resistance to low temperature cracking of asphalt pavement. However, while Bonaquist's study did not show such an effect, some other studies have reported that the addition of wax might increase the low temperature grade by 2-3°C (Wanger et al 2008;Chowdhury and Button 2008) and Fraas temperature by 1-5°C (Zaumanis et al 2012b).…”
Section: Crackingmentioning
confidence: 52%
“…The methods for compensating for the aged, stiff binder and ensuring adequate pavement performance include the use of rejuvenating or softening additives, use of softer virgin binder grade and increase in total mixture binder content (Tran et al 2012). The utilisation of warm mix technologies can reduce further ageing of binder (Zaumanis et al 2012b). These methods are discussed in Section 6.…”
Section: Aged Bindermentioning
confidence: 98%
“…The reduced mixing temperature of WMA significantly limits the undesirable ageing process which compensates for stiffer RAP bitumen . Most WMA technologies also provide temporary reduction of bitumen viscosity and/or improve lubrication that allows to sufficiently coat the aggregates and improve workability International Journal of Pavement Engineering 47 without raising the temperature (Arnold et al 2012, Zaumanis et al 2012b. .…”
Section: Warm MIX Asphaltmentioning
confidence: 99%
“…On the other hand high amount of wax in bitumen does not limit its usefulness as a material for the pavement construction and some new generations of wax additives can improve binder properties, e.g. stiffness and viscosities at service intermediate temperatures [10,11,14] and rutting resistance [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%